The symphonic music of the national schools in 20th century Europe in the repertoire of the Philharmonic of Cluj (1955-1989). Creative perspectives of C. Silvestri’s Chants Nostalgiques op. 27 no. 1 - Spiridon, Simona (Journal of Education Culture and Society, 2020)
The present work focuses on the national cultures of the early 20th century in several European countries, such as Czechoslovakia, Poland, Hungary, Spain, Russia and Romania. Since my PhD thesis analyses the evolution of the Philharmonic “Transilvania”of Cluj between 1955-1989, there will be a thorough statistic of the concerts which were held during that period in which the orchestra performed musical pieces of the composers mentioned in this essay. For some concerts, there will also be stated the date when the concert took place, as well as the conductor who was invited to Cluj. There will also be an analysis of a piano work of the Romanian composer Constantin Silvestri (Chants Nostalgiques op. 27 no. 1) which I personally played a few years ago. The study will contain a musical bibliography, as well as several footnotes stating the documents found in the archives of the Philharmonic of Cluj.